2023
DOI: 10.3390/ijerph20186794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Food Literacy and Food Security through School Gardening in Rural and Regional Communities

Timothy P. Holloway,
Sisitha Jayasinghe,
Lisa Dalton
et al.

Abstract: A qualitative case study approach with in-depth, semi-structured interviews of key school staff, and student feedback was used to assess a school kitchen and garden program in the regional area of North-West Tasmania, Australia. A detailed program description was produced to conduct a realist evaluation with a Context-Mechanism-Outcome configuration, followed by a program theory evaluation through the construction of a retrospective program logic model. Dedicated kitchen and garden spaces, knowledgeable teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…It meant that many learners were able to contribute to the activities and to the collective creation and sharing of knowledge building on their experience from home. The gardens also allow for experiential learning, which supports the findings of multiple studies (Block et al, 2012;Williams and Dixon, 2013;Holloway et al, 2023). While many learners might struggle to recall what they learnt in class during 2023, there is a high likelihood that as a group they will be able to piece together a story about the gardens from the start to the finish, and will be able to perform the songs that they created, despite the project having finished some months ago.…”
Section: Beyond the Project Towards Mainstreaming Food Gardens As A L...supporting
confidence: 57%
See 1 more Smart Citation
“…It meant that many learners were able to contribute to the activities and to the collective creation and sharing of knowledge building on their experience from home. The gardens also allow for experiential learning, which supports the findings of multiple studies (Block et al, 2012;Williams and Dixon, 2013;Holloway et al, 2023). While many learners might struggle to recall what they learnt in class during 2023, there is a high likelihood that as a group they will be able to piece together a story about the gardens from the start to the finish, and will be able to perform the songs that they created, despite the project having finished some months ago.…”
Section: Beyond the Project Towards Mainstreaming Food Gardens As A L...supporting
confidence: 57%
“…A number of studies have found that the usefulness of gardens as a tool for enriching the learning environment depends on the buy-in of knowledgeable staff with access to necessary resources, as well as attention to curriculum development to support the integration of classroom and outdoor learning processes (Williams and Dixon, 2013;Holloway et al, 2023). The TESF project has initiated very useful discussion and exchange of ideas between NGO staff and educators about the benefits of food gardens and alternative teaching methods and provides a sound basis for future work of this nature.…”
Section: Beyond the Project Towards Mainstreaming Food Gardens As A L...mentioning
confidence: 99%